Risk factors of student failure in a blended learning instruction during COVID-19 pandemic - Erlinda Dacara Tibus; Jahara Dagangan Napalla; Sybill Krizzia Gabronino Ledesma (International Journal of Evaluation and Research in Education (IJERE), 2023)
With the advent of COVID-19, universities abruptly shifted to blended learning instruction to suit the necessity of education despite the pandemic. This emerging course design has led to an increase in the number of blended courses in higher education. It came with advantages, especially in the time of the pandemic. However, this type of instruction has brought risk factors of student failure. In this study, through exploratory factor analysis, it was identified that four factors had affected the students at risk of failure in a blended learning instruction, they were: i) Virtual environment; ii) Degree of intrinsic motivation; iii) Virtual classroom conduct; and iv) Perceived inability. Students were found to be experiencing these factors, which hinder their performance in the blended learning modality. These students have needs that must be attended to. Therefore, there is a need to modify existing teaching approaches that best suit and cater to these needs in a blended or virtual classroom setup.